Natural resource sovereignty and the right to development in Africa - Ngang, Carol Chi; Kamga, Serges Djoyou (Serges Alain Djoyou) (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"This book explores the nexus between natural resources ownership and the right to development in Africa. The right to sovereignty over natural resources and the right to development are recognised and protected in an extensive framework of international, regional and domestic instruments. They guarantee people's entitlement to fully and freely utilise their natural resources as a means of subsistence and for economic, social and cultural development. Yet, despite the abundance of natural resources in Africa a majority of the people on the continent remain largely impoverished. This book articulates the central argument that to achieve the right to development in Africa requires appropriate governance of the continent's natural resources to which the people of Africa are guaranteed sovereign ownership. With case study illustrations from Zimbabwe, Ghana, Ethiopia and the Democratic Republic of Congo, chapters explore the normative measures, specific guarantees and community entitlements to natural resources for the realization of the right to development. The book will be an invaluable guide to scholars and postgraduate students of Natural Resources, Development and African studies as well as policymakers and practitioners in these areas"--
The natural resource and right to development dilemma / Serges Djoyou Kamga and Carol Chi Ngang -- Sustainable right to development governance of natural resources in Africa / -- Carol Chi Ngang -- Loss, anguish and postponement: The story of African development, natural resource ownership and the paradox of waiting / Isaac Shai -- Rationale for Africa's 'legitimate' ownership of her natural resources / Daphine Kabagambe Agaba -- Resource constitutionalism for socio-economic development in Africa's petrostates: Re-imagining prior-informed consent -- Aaron Olaniyi Salau -- Peoples' right to natural resources in Africa and state sovereignty: A quest for equilibrium / Jacob Osutongun Abiodun -- Colonial extraction of natural resource and the impact on the right to development in Africa / Annelie de Man and Carol Chi Ngang -- Issues of sovereignty over natural resources in Africa / Faith Kabata -- Rethinking natural resource ownership and the realisation of the right to development for indigenous peoples in Africa / Esther E. Njieassam -- Ownership of natural resources and the right to development for African indigenous peoples / Ebun Abolarin -- Assessing the impact of water policies and practices on the RTD within the tourism industry in Africa / Furaha Joy Sekai Saungweme -- Sustainable Development Goals and the bumpy road to 2030 in Ethiopia: The challenges of land grabbing / Jean-Claude N. Ashukem -- Freedom from want and the constitutional right to development in Ethiopia: Urban Productive Safety Net Programme-The case of Addis Ababa / Tsion T. Dechassa and Gedion G. Jalata -- Corporate social responsibility and the right to development in local communities: The case of the Democratic Republic of Congo / Muyamba Mangu and Serges Djoyou Kamga -- Laws on natural resources ownership in Ghana: A perceived hindrance to community development / Bridget Kafui Anthonio-Apedzi -- Policy implications of the right to development through the Mining Charter of South Africa / Mofihli Teleki -- Impact of artisanal and small scale gold mining on livelihood in Mutasa District of Manicaland Province, Zimbabwe / Cephas Mandihrawe -- Conclusion. Towards a resilient development future in Africa / Carol Chi Ngang.
Includes bibliographical references and index.
Keywords: Natural resources -- Africa -- Management; Law and economic development -- Africa; Sustainable development -- Africa; Law and economic development; Natural resources -- Management; Sustainable development; Africa